Challenges and Complications of Long-Term Screen Exposure: An Editorial Letter - Niroumand Sarvandani, Mohammad; Rafaiee, Raheleh; Kalalian-moghaddam, Hamid (Shahroud Journal of Medical Sciences, 2025)
The persistent exposure of children and adolescents to screens is a growing global problem whose complications are gradually involving societies. The prevalence of screen addiction among adolescents varies considerably from country to country, and the results of recent studies are remarkable. Among the countries studied, Brazil has the highest prevalence, with an incredible 70.9% of adolescents spending excessive time on screens1. In contrast, studies from Switzerland show that while screen use has increased dramatically, rates of problematic screen use have remained stable without a significant increase in Internet Addiction Test scores2,3. In China, the prevalence of Internet addiction among young people is reported to be 6.2%, which is a lower rate than in Brazil4. In Northern Cyprus, the prevalence of Internet addiction among young people is 18.15.